SP1-Induced Upregulation of lncRNA LINC00659 Promotes Tumour Progression in Gastric Cancer by Regulating miR-370/AQP3 Axis - Wang, Yao; Guo, Yuanyuan; Zhuang, Tianchi; Xu, Ting; Ji, Minghui (Frontiers in Endocrinology, 2022)
Growing evidence demonstrates that long noncoding RNAs (lncRNAs) play critical roles in various human tumors. LncRNA LINC00659 (LINC00659) is a newly identified lncRNA and its roles in tumors remain largely unclear. In this study, we elucidated the potential functions and molecular mechanisms of LINC00659 on the biological behaviors of gastric cancer (GC), and also explored its clinical significance. We firstly demonstrated LINC00659 levels were distinctly up-regulated in both GC specimens and cells using bioinformatics analysis and RT-PCR. The results of ChIP assays and luciferase reporter assays confirmed that upregulation of LINC00659 was activated by SP1 in GC. Clinical assays revealed that higher levels of LINC00659 were associated with TNM stage, lymphatic metastasis and poorer prognosis. Moreover, LINC00659 was confirmed to be an independent prognostic marker for the patients with GC using multivariate assays. Lost-of-function assays indicated that knockdown of LINC00659 suppressed the proliferation, metastasis and EMT progress of GC cells in vitro. Mechanistic investigation indicated that LINC00659 served as a competing endogenous RNA (ceRNA) for miR-370, thereby resulted in the upregulation of leading to the depression of its endogenous target gene AQP3. Overall, our present study revealed that the LINC00659/miR-370/AQP3 axis contributes to GC progression, which may provide clues for the exploration of cancer biomarkers and therapeutic targets for GC.